Implemetnasi Strategi Pembelajaran Inquiry pada Mata Pelajaran SKI - sinaga, mitha shaskila; Arlina, Arlina; Tumanggor, Nurjannah; Hidayah, Astriana; Bayani Situmorang, Hikmah (Yayasan Lembaga Studi Makwa, 2023)
Through learning activities, there is a relationship between educators and students and several components that influence it. The components in it are closely related to the teaching and learning process, such as: teachers, students, curriculum, methods and elements that support the process of providing education. In improving the quality of teaching and learning, the application of learning strategies is a fundamental thing that must be chosen. The inquiry strategy is one of the learning strategies that emphasizes students to be more active in the teaching and learning process. This study intends to examine that the inquiry strategy is a suitable strategy to be applied to SKI learning. This study uses a literature study method that uses primary sources in the form of books and authoritative journals. Through this analysis, it is expected to be a reference material related to problems in implementing learning strategies, especially regarding SKI lessons. From the analysis that has been done, it can be concluded that the inquiry learning strategy is very appropriate or relevant to be applied to SKI subjects because it can motivate students to develop their potential. Abstrak Artikel ini bertujuan untuk mengkaji apakah strategi inkuiri merupakan strategi yang cocok diterapkan pada pembelajaran SKI. Dalam proses pembelajaran membentuk terjadinya hubungan antara pendidik dan peserta didik serta beberapa komponen yang mempengaruhinya. Komponen-komponen di dalamnya berkaitan erat dengan proses belajar mengajar, seperti: guru, siswa, kurikulum, metode dan unsur-unsur yang mendukung proses penyelenggaraan pendidikan. Penelitian ini menggunakan metode studi pustaka yang menggunakan sumber primer berupa buku dan jurnal otoritatif. Melalui analisis ini diharapkan dapat menjadi bahan acuan terkait permasalahan dalam penerapan strategi pembelajaran khususnya mengenai pelajaran SKI. Dari analisis yang telah dilakukan ditemukan bahwa strategi pembelajaran inkuiri sangat tepat atau relevan diterapkan pada mata pelajaran SKI karena dapat memotivasi siswa untuk mengembangkan potensi dirinya.